Angiolymphoid Hyperplasia with Eosinophilia That Was Possibly Induced by Vaccination in a Child - Jeon, Eun-Kyoung (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2009)
Angiolymphoid hyperplasia with eosinophilia (ALHE) is a rare benign vasoproliferative disease of an unknown cause involving the skin or subcutaneous tissue of the head and neck, and particularly around the ear. It predominantly affects Caucasian adults during the third and fourth decades and it very rarely occurs in children. We experienced a case of ALHE in a 2-year-old Korean boy who had a firm, pruritic, skin-colored, subcutaneous nodule on his right upper arm. The histopathological findings were compatible with ALHE and they showed prominent vascular changes with epitheloid or histiocytoid endothelial cells surrounded by inflammatory cells, including a large proportion of eosinophils. This unusual distribution of the lesion and the young age of the patient may be associated with vaccination.